SOCIAL CONTROL IN THE CONTEXT OF THE ASSOCIATION OF LOCAL COMMUNITIES AND DECENTRALIZATION IN UKRAINE - Boklah V.A.; Pavlenko A.O. (Pressing Problems of Public Administration, 2017)
The article deals with the role and special importance of public scrutiny as a system of control over the state apparatus and local government bodies. It substantiates the need to establish public councils as a coordination body to exercise public control. The article highlights the importance of holding general meetings and public hearings as an ef cient mechanism of monitoring the activities of local government and executive bodies.